When the wind blows - Patterson, James, 1947- (Vision, 1999)
Frannie O'Neill, a young and talented veterinarian whose husband was recently murdered, comes across an amazing discovery in the woods near her animal hospital. Soon after, Kit Harrison, an unconventional FBI agent, arrives on Frannie's doorstep. And then there's the child loose in the back woods, 11 year-old Max, one of the most unforgettable and startling creations in thriller fiction.